2017
DOI: 10.5144/0256-4947.2017.362
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of glucose-6-phosphate dehydrogenase deficiency in neonates in Egypt

Abstract: BACKGROUNDGlucose-6-phosphate dehydrogenase (G6PD) deficiency is an X-linked disorder which causes neonatal jaundice in most cases, and under certain conditions, can cause a spectrum of hemolytic manifestations.OBJECTIVETo determine the local prevalence of G6PD deficiency in newborns.DESIGNCross-sectional.SETTINGUniversity hospital.METHODSInfants born during 2015 were prospectively screened for G6PD deficiency. Dried blood spot samples on filter paper were collected in collaboration with the central laboratori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 22 publications
(24 reference statements)
5
16
0
2
Order By: Relevance
“…Ultraviolet-kinetic method using cellular enzyme determination reagents by spectrophotometry was used to obtain a quantitative estimation of serum G6PD from 1 mL of whole blood collected in an EDTA tube. G6PD deficiency was defined as <4.6 g/L Hb 10. The neonates were subjected to phototherapy according to phototherapy guidelines for hospitalised infants from ≥35 weeks of gestation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultraviolet-kinetic method using cellular enzyme determination reagents by spectrophotometry was used to obtain a quantitative estimation of serum G6PD from 1 mL of whole blood collected in an EDTA tube. G6PD deficiency was defined as <4.6 g/L Hb 10. The neonates were subjected to phototherapy according to phototherapy guidelines for hospitalised infants from ≥35 weeks of gestation.…”
Section: Methodsmentioning
confidence: 99%
“…Based on a previous review of literature10 which reported an 8.9% prevalence of G6PD among newborns with jaundice with nearly the same inclusion and exclusion criteria as our study, the sample size was calculated using the following equation: n=(z 2 ×p×q)/D2, at 95% CI. The sample size was estimated to be 487 neonates with jaundice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In G6PD deficiency, haemolysis is usually triggered by exogenous agents. The G6PD gene is located in chromosome X and therefore its deficiency is more common in males than females 2 . Patients with G6PD deficiency can be clinically asymptomatic or present with neonatal jaundice or acute haemolytic anaemia 3 .…”
Section: Introductionmentioning
confidence: 99%